Comparison of intrahepatic progression patterns of hepatocellular carcinoma and colorectal liver metastases following CT-guided high dose-rate brachytherapy. (September 2021) - Xu, Han; Schmidt, Robin; Hamm, Charlie Alexander; Schobert, Isabel Theresa; He, Yubei; Böning, Georg; Jonczyk, Martin; Hamm, Bernd; Gebauer, Bernhard; Savic, Lynn Jeanette
Introduction: Given the metachronous and multifocal occurrence of hepatocellular carcinoma (HCC) and colorectal cancer metastases in the liver (CRLM), this study aimed to compare intrahepatic progression patterns after computed tomography (CT)-guided high dose-rate brachytherapy. Patients and methods: This retrospective analysis included 164 patients (114 HCC, 50 CRLM) treated with brachytherapy between January 2016 and January 2018. Patients received multiparametric magnetic resonance imaging (MRI) before, and about 8 weeks after brachytherapy, then every 3 months for the first, and every 6 months for the following years, until progression or death. MRI scans were assessed for local or distant intrahepatic tumor progression according to RECIST 1.1 and electronic medical records were reviewed prior to therapy. The primary endpoint was progression-free survival (PFS). Specifically, local and distant intra-hepatic PFS were assessed to determine differences between the intrahepatic progression patterns of HCC and CRLM. Secondary endpoints included the identification of predictors of PFS, time to progression (TTP), and overall survival (OS). Statistics included Kaplan–Meier analysis and univariate and multivariate Cox regression modeling. Results: PFS was longer in HCC [11.30 (1.33–35.37) months] than in CRLM patients [8.03 (0.73–19.80) months, p = 0.048], respectively. Specifically, local recurrence occurred later in HCC [PFS: 36.83 (1.33–40.27) months] than CRLM patients [PFS: 12.43 (0.73–21.90) months, p = 0.001]. In contrast, distant intrahepatic progression occurred earlier in HCC [PFS: 13.50 (1.33–27.80) months] than in CRLM patients [PFS: 19.80 (1.43–19.80) months, p = 0.456] but without statistical significance. Multivariate Cox regression confirmed tumor type and patient age as independent predictors for PFS. Conclusion: Brachytherapy proved to achieve better local tumor control and overall PFS in patients with unresectable HCC as compared to those with CRLM. However, distant progression preceded local recurrence in HCC. As a result, these findings may help design disease-specific surveillance strategies and personalized treatment planning that highlights the strengths of brachytherapy. They may also help elucidate the potential benefits of combinations with other loco-regional or systemic therapies.